Turnover intention among Malaysian operators in electrical and electronics sub-sector: Leadership style perspective - Md Nor, Nik Norsyamimi; Omar, Zainudin; Sumilan, Helmi; Heng, Chin Siong; Johari, Husna (2014)
Job turnover is traditionally faced by organizations in many industries.Resource wastage and low productivity can be derived from turnover issue.Turnover intention was found to be a reliable predictor of actual turnover in previous studies.Consequently, this cries for some insights on turnover intention issue, especially within Malaysian context.This paper will concentrate on determining the relationship of leadership style on turnover intention among manufacturing operators in focusing on Electrical and Electronics sub-sector.The survey was taken amongst the operators of manufacturing industry in Peninsular Malaysia (N=800).Considering that Malaysia manufacturing industry has recorded a substantial economic growth through heavy investment in economic activities, it is significant for all manufacturing companies to retain talented employees and reduce turnover problem in order to be more competitive.The findings had accepted the research hypothesis. Dimensions of leadership style (i.e.transactional) had significantly correlated and contributed to the turnover intention.The findings had contributed to the theoretical significance through the examination of direct relationships between leadership style on turnover intention among local operators in manufacturing sector based on the high turnover rate in Malaysia manufacturing sector between the years 2008 until early of 2011.